The Elusive Faces of Modernity: Jacques Gréber and the Planning of the 1937 Paris World Fair - Udovicki-Selb, Danilo (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2001)
The occasion of the first commission that Jacques Gréber received to plan the new city centre of Ottawa—the 1937 Paris International Exposition—was the scene of the first encounter between the proponents of the New Architecture and the tenets of the "Retour à l'Ordre." The last in the long tradition of French "Universelles," with their common eighteenth-century Illuminist legacy, the exposition Gréber planned was the first to open its doors widely to the most radical modern arts. This article argues that Gréber based the exposition on a double refusal: On the one hand, the refusal to introduce a unique controlling style, as had been the case in all previous French fairs, and on the other the refusal to represent modernity in any single-minded form. This pluralist approach announced in France the end of modernity understood as an issue of style altogether.